Questões conceituais da análise do comportamento e neurociências na interface com educação - OLIVEIRA, Julio Cezar Pereira de (Universidade Federal do Pará, 2022)
Currently the work performed by different professionals in the face of a common demand (multi/inter/transdisciplinary work) is required in several knowledge application environments, among them the hospital, organizations and schools. This multi-looking work on the same object has also been developed in the field of scientific research. The objective of this study was to discuss points of convergence and theoretical divergences between Behavior Analysis and Neurosciences within the interface with the educational context. For this, a theoretical study was produced. Initially, a survey of behavioral and neuroscience analytical literature was carried out with educational bias. Later, the selected material was read and analyzed through two pre-defined categorization steps according to the objectives of the present study. It was found that both areas have significant production in the interface with education, with a variety of topics discussed and researched. The convergences found were about the role of the educator, which for the authors of both areas should be based on their theoretical assumptions. Disagreements were about the characterization of education / education. For Behavior Analysis, educating concerns the gaining of preparatory skills for group living and environmental manipulation. For neurosciences, education is related to changes in brain structures. It was concluded that the method used did not benefit that a significant sample of the literature was raised, considerably impairing the presentation of convergences and divergences between the two areas, making the study direction, substantially based on the similarity and differences survey, ineffective in Present the relevant points worked in the two fields of study. However, some of the objectives were achieved, and the present work was able to point out what is being produced at the interface between the researched areas.